2019
DOI: 10.1126/sciadv.aaw0254
|View full text |Cite
|
Sign up to set email alerts
|

The innate immune sensor Toll-like receptor 2 controls the senescence-associated secretory phenotype

Abstract: Cellular senescence is a stress response program characterized by a robust cell cycle arrest and the induction of a proinflammatory senescence-associated secretory phenotype (SASP) that is triggered through an unknown mechanism. Here, we show that, during oncogene-induced senescence (OIS), the Toll-like receptor 2 (TLR2) and its partner TLR10 are key mediators of senescence in vitro and in murine models. TLR2 promotes cell cycle arrest by regulating the tumor suppressors p53-p21CIP1, p16INK4a, and p15INK4b and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 55 publications
4
92
0
Order By: Relevance
“…3A). Among them, FOXA1, PLAT, CD44, FGF5, DIO2 and other genes are upregulated, whereas PLCB1, SETBP1, EHD3, ZNF423, PHGDH and other genes are downregulated in multiple senescence systems(Chan et al, 2019; Cho et al, 2019; Galanos et al, 2016; Hari et al, 2019; Hernandez-Segura et al, 2017; Komseli et al, 2018; Lau, Porciuncula, Yu, Iwakura, & David, 2019; Leveque et al, 2019; Q. Li et al, 2013; Limbad et al, 2020; Lowe & Raj, 2014; Nagano et al, 2016; Pan et al, 2019; Pantazi et al, 2019; Suwan et al, 2009; Wu, Pepowski, Takahashi, & Kron, 2019; Zhou et al, 2010), as are consistent with our results.…”
Section: Resultssupporting
confidence: 92%
“…3A). Among them, FOXA1, PLAT, CD44, FGF5, DIO2 and other genes are upregulated, whereas PLCB1, SETBP1, EHD3, ZNF423, PHGDH and other genes are downregulated in multiple senescence systems(Chan et al, 2019; Cho et al, 2019; Galanos et al, 2016; Hari et al, 2019; Hernandez-Segura et al, 2017; Komseli et al, 2018; Lau, Porciuncula, Yu, Iwakura, & David, 2019; Leveque et al, 2019; Q. Li et al, 2013; Limbad et al, 2020; Lowe & Raj, 2014; Nagano et al, 2016; Pan et al, 2019; Pantazi et al, 2019; Suwan et al, 2009; Wu, Pepowski, Takahashi, & Kron, 2019; Zhou et al, 2010), as are consistent with our results.…”
Section: Resultssupporting
confidence: 92%
“…A recent study shows the involvement of Toll-like receptor 2 (TLR2) via the TP53, p16 and p15 pathways, thereby inducing cell cycle arrest and induction of acute-phase serum amyloids, which are part of damage-associated molecular patterns (DAMP). DAMPs in turn signal through pattern recognition receptors of the innate immune system such as TLR2, thereby controlling the SASP and reinforcing cell cycle arrest during senescence [26].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we demonstrated that low activity of TLR2 and TLR5 regulated SASP secretion in small cells from MSCs. Studies have already reported that TLR2 and TLR5 are important factors in the regulation of cellular senescence [ 45 , 46 ]. According to Hari et al, innate immune sensing of senescence-related damage-associated molecular patterns (DAMPs) by TLR2 mediated the SASP and improved the cell cycle arrest program in oncogene induce senescence (OIS) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%